Physiological characteristics of male basketball players during pre-season phase: a pilot study - Jallai, T.; Ereline, J.; Kums, T.; Aibast, H.; Gapejeva, H.; Pääsuke, M. (Acta Kinesiologiae Universitatis Tartuensis, 2011)
The purpose of this pilot study was to determine the changes in physiological characteristics in male basketball players throughout different training periods. Twenty-seven male basketball players, age ranging from 14 to 27 years, were distributed into 3 groups: I group consisted of elite male basketball players (n=4, mean age and SD 23±3.8 yrs), II group consisted of development team basketball players (n=12, mean age 17.5±1 yrs), and III group consisted of young basketball players (n=11, mean age 15±0.6 yrs). The subjects performed static balance, muscle power, strength and endurance tests, and their body composition was also determined. The subjects filled in a questionnaire that included anthropometric data, physical activity level, and history of injuries. Anthropometric data, characteristics of static standing balance, vertical jumps and leg extensor muscle and quadriceps femoris muscle isometric maximal voluntary contraction force; also one-mile jogging test, T-test, the running-based anaerobic sprint test, static and dynamic core exercises estimations were recorded in August 2010, at the end of the basketball players` pre-season training phase. The battery of tests gives a comprehensive overview of 92 Presentations of the Fourth Baltic Conference physiological characteristics of well-trained male basketball players. Mixed modeling will be used to estimate mean changes within and between phases of one year and covering several years.